Normative distribution of corneal epithelial thickness on 9-mm OCT maps - Morgado, Claudia R.; Santhiago, Marcony R. (Frontiers in Medicine, 2025)
This prospective observational study comprehensively characterized the normative distribution of corneal epithelial thickness using 9-mm spectral-domain optical coherence tomography (SD-OCT) maps. Data were collected from 283 eyes of refractive surgery candidates who underwent a complete ophthalmologic evaluation, including SD-OCT imaging. The analysis revealed a mean central corneal epithelial thickness of 53.34 μm (SD ± 3.26 μm), exhibiting a heterogeneous distribution with significantly thicker measurements in inferior compared to superior regions. This distribution followed a Gaussian pattern, with the thickest measurements consistently observed in the central and inferior regions. The study also revealed statistically significant differences in central corneal epithelial thickness between males (54.11 μm) and females (52.64 μm). A weak but significant negative correlation was observed between superior epithelial thickness and age. This detailed analysis of corneal epithelial thickness across multiple zones within a large sample provides valuable normative data essential for clinical practice and future research in corneal pathology. The established normative reference values are critical for accurately identifying deviations in epithelial thickness associated with conditions such as keratoconus.